Mental illness and the Shona People - Muchinako, George Alex; Mabvurira, Vincent; Chinyenze, Patience (2020)
The study sought to assess some of the key issues on mental illness among the Shona society in Zimbabwe. Information was collected from documents and key informant interviews. The study found out that the Shona definition of mental illness is similar to the western view but they have a different view on the causes. They believe that there is always a supernatural influence behind any mental illness problem. To deal with mental illness the Shona use a combination of approaches: the traditional medical doctor, the faith healer and the western medical doctor. The Shona prefer to consult the traditional doctor or the spiritual and faith healer before the western medical doctor and will often leave the modern hospital to seek treatment from the traditional doctor. The lack of adequate psychiatric services and lack of educational awareness on mental health issues in a fast changing and modernizing Zimbabwe continue to leave the Shona with the strong belief in the importance of metaphysical solutions to mental illness issues.